2018
DOI: 10.1002/ejoc.201800361
|View full text |Cite
|
Sign up to set email alerts
|

A Consecutive Four‐Component Synthesis of Polysubstituted Thiophenes in Aqueous Medium

Abstract: An efficient and straightforward four‐component synthesis of mono‐, bi‐ and tricyclic thiophenes from C–C + C + C + S atom fragments from 1,3‐dicarbonyl compounds, aldehydes, activated methylene halides and elemental sulfur in aqueous medium is described. Arylidene‐1,3‐dicarbonyls, N‐phenacylpyridinium bromides/N‐(p‐nitrobenzyl)pyridinium chloride, pyridinium ylides and 2,3‐dihydrofurans are believed to be the key intermediates of these consecutive transformations. This synthetic strategy provides a potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 77 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…hyde 12 and α-pyridiniumacetophenone bromide 14 (generated from reaction between phenacyl bromide 13 and pyridine). [5] Likewise, 1,3-diketo compounds such as 4-hydroxycoumarine, ethyl acetoacetate, dimedone and cyclohexa-1,3-dione could be used in place of penta-2,4dione, whereas p-nitrobenzyl chloride displayed the same reactivity in this kind of multicomponent reactions. Selected examples were shown in Scheme 5.…”
Section: Elemental Sulfur Acting As a Sulfur Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…hyde 12 and α-pyridiniumacetophenone bromide 14 (generated from reaction between phenacyl bromide 13 and pyridine). [5] Likewise, 1,3-diketo compounds such as 4-hydroxycoumarine, ethyl acetoacetate, dimedone and cyclohexa-1,3-dione could be used in place of penta-2,4dione, whereas p-nitrobenzyl chloride displayed the same reactivity in this kind of multicomponent reactions. Selected examples were shown in Scheme 5.…”
Section: Elemental Sulfur Acting As a Sulfur Sourcementioning
confidence: 99%
“…While the reaction conditions were relatively complex with the involvement of copper-TEMPO-2,2'-bipyridine catalysts and tetrabutylammonium acetate as an ionic reaction medium, the reaction followed the same pathway as for the reaction of o-nitrochalcones with sulfur in the presence of a tertiary amine previously described by our group (Section 2.2.1). [16,17] Huang et al reported a copper-catalyzed threecomponent access to a variety of benzo [4,5]thieno [3,2c]isoquinoline and thieno[3,2-c]isoquinoline 105 from methylketoxime acetates 103, o-halobenzaldehydes 104, and elemental sulfur (Scheme 39). [39] It was postulated that 3-aminobenzothiophene would be formed from sulfuration of acetophenone oxime acetate.…”
Section: Thiophenes Fused With Fused Pyridinesmentioning
confidence: 99%
See 1 more Smart Citation
“… The traditional approach to obtaining 2-acylthiophenes relies on late-stage modification via the Friedel–Crafts acylation of thiophenes using specific Lewis acid promoters combined with acyl anhydrides or acid chlorides, which often provides poor atom economy and/or deleterious environmental effects . However, the synthesis of 2-acylthiophenes has received little attention and, to the best of our knowledge, there have been no reports to date concerning the straightforward synthesis of 2,4-diacylthiophenes from alkynes …”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the first approach, thieno[3,2-c]coumarins were synthesized by four-component reaction of 4-hydroxycoumarin, phenacyl bromides, aromatic aldehydes and elemental sulfur. The reaction was mediated by pyridine and involved the use of both trimethylamine and morpholine as catalysts 40 . Moreover, thieno[3,2-c]coumarins were prepared by the reaction of chalcones, 4-hydroxycoumarin and elemental sulfur.…”
mentioning
confidence: 99%